Popliteal artery entrapment syndrome as a cause of failed treatment of a false popliteal aneurysm - Song, Xitao (J Int Med Res, 2019)
OBJECTIVE: Popliteal artery entrapment syndrome is a rare cause of popliteal artery aneurysms. We present a rare case of a false aneurysm associated with popliteal artery entrapment syndrome that was treated with endovascular repair that initially failed. CASE REPORT: A 60-year-old man with a false popliteal artery aneurysm and limb ischemia was treated with endovascular repair that initially failed. The popliteal artery was suspected to be compressed by an abnormal bundle of muscle according to the findings of a subsequent magnetic resonance imaging examination. The popliteal artery was entrapped by an abnormal slip of the medial gastrocnemius muscle head. Parts of the popliteus muscle were also involved in compression of the popliteal artery, which was not distinguished on preoperative magnetic resonance imaging. Thus, the patient was diagnosed with a mixed type of popliteal artery entrapment syndrome (types III and IV). Bypass with the small saphenous vein was then performed. The patient was finally discharged with satisfactory relief of his ischemic symptoms. CONCLUSION: Popliteal artery entrapment syndrome should be considered before treating popliteal artery aneurysms, especially atypical pseudoaneurysms without significant atherosclerosis. Definitive surgical management rather than endoluminal treatment is required unless combined with open decompressive surgery to correct the musculotendinous anatomy.